2018
DOI: 10.1371/journal.pone.0188509
|View full text |Cite
|
Sign up to set email alerts
|

Synchrotron microtomography of a Nothosaurus marchicus skull informs on nothosaurian physiology and neurosensory adaptations in early Sauropterygia

Abstract: Nothosaurs form a subclade of the secondarily marine Sauropterygia that was well represented in late Early to early Late Triassic marine ecosystems. Here we present and discuss the internal skull anatomy of the small piscivorous nothosaur Nothosaurus marchicus from coastal to shallow marine Lower Muschelkalk deposits (Anisian) of Winterswijk, The Netherlands, which represents the oldest sauropterygian endocast visualized to date. The cranial endocast is only partially encapsulated by ossified braincase element… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 167 publications
(274 reference statements)
2
13
0
Order By: Relevance
“…Plesiosaurian olfactory tracts, elongated anteroposteriorly and not separated along their length (Fig. 3), are similar to those reported in mosasauroids and nothosaurians (Camp, 1942;Voeten et al, 2018) but differ from the short olfactory tracts observed in turtles (Paulina-Carabajal et al, 2013) and the more or less separated olfactory tracts found in snakes (Allemand et al, 2017c), thalattosuchians (e.g., Pierce et al, 2017) and ichthyosaurs (e.g., Marek et al, 2015). Plesiosaurian endocasts are nearly linear (Fig.…”
Section: Comparisons With Extinct and Extant Marine Reptilessupporting
confidence: 78%
See 3 more Smart Citations
“…Plesiosaurian olfactory tracts, elongated anteroposteriorly and not separated along their length (Fig. 3), are similar to those reported in mosasauroids and nothosaurians (Camp, 1942;Voeten et al, 2018) but differ from the short olfactory tracts observed in turtles (Paulina-Carabajal et al, 2013) and the more or less separated olfactory tracts found in snakes (Allemand et al, 2017c), thalattosuchians (e.g., Pierce et al, 2017) and ichthyosaurs (e.g., Marek et al, 2015). Plesiosaurian endocasts are nearly linear (Fig.…”
Section: Comparisons With Extinct and Extant Marine Reptilessupporting
confidence: 78%
“…Plesiosaurian endocasts are nearly linear (Fig. 3), both the anterior and posterior parts being at the same dorsoventral level, similarly as reported in snakes (Allemand et al, 2017c), thalattosuchians (e.g., Pierce et al, 2017), nothosaurians (Voeten et al, 2018) and turtles (Paulina-Carabajal et al, 2013), a condition differing from that of Placodus gigas (Neenan and Scheyer, 2012), in which the structure appears anteroposteriorly inclined and sigmoidal. The horizontal projection of the plesiosaurian pituitary differs from the tilted one observed in snakes (Allemand et al, 2017c) and thalattosuchians (e.g., Pierce et al, 2017).…”
Section: Comparisons With Extinct and Extant Marine Reptilessupporting
confidence: 72%
See 2 more Smart Citations
“…This well-dated section, palynologically constrained at the Anisian (247.2-242 Ma;Herngreen et al 2005), has a rich fossil fauna, which has been subject to numerous palaeontological studies. These recovered ichnofossils and tetrapod footprints (Oosterink 1976;Demathieu and Oosterink 1988;Diedrich 2000;Schulp et al 2017), reptiles (nothosaurs and placodonts) (Albat 1999;Bickelmann and Sander 2008;Klein 2009Klein , 2012Klein and Albers 2009;Albers 2011;Klein and Scheyer 2013;Klein and Sichelschmidt 2014;Sander et al 2014;Klein et al 2015Klein et al , 2016Voeten et al 2015Voeten et al , 2018Maxwell et al 2016;During et al 2017;Klein and Griebeler 2018;Heijne et al 2019), but also lobsters (Klompmaker and Fraaije 2011), jellyfish (Klompmaker and Fraaije 2011), and insects (van Eldijk et al 2017). The Muschelkalk Formation contains widespread secondary mineralizations in cracks and pores, containing like pyrite and celestine (Kloprogge et al 2001).…”
Section: Geological Setting and Samplingmentioning
confidence: 99%